The Role of Nearpod Learning Media in Increasing Participation and Learning Outcomes - Anggaretta, Dhela Septian; Dewi, Dyah Mustika Chandra; Hardiyanti, Dian; Ahyuni, Vinasya Adella; Langit, Nabila Sekar; Santoso, Jarot Tri Bowo Santoso (Economic Education Analysis Journal, 2024)
This study aimed to determine the effectiveness of nearpod-based interactive learning media on general journal material in increasing student participation and learning outcomes in introductory trading company accounting courses. This research uses a form of class quasi experimental research with one group pretest and posttest. The research subjects were students of the Department of Office Administration Education A Class of 2023 Semarang State University and were sampled using a saturated sampling technique with totaling 50 students. Data collection techniques involved using tests in the form of pre-test and post-test, and observation. The data analysis technique employed the T-test and documentation. The results show that (1) nearpod interactive media is effectively used in the learning process of general journals of trading companies. The average of pre-test score increases from 4.08 to 8.30 after applying nearpod learning media; and (2) Student participation increases by 33% from 49% to 82% after using nearpod learning media.